Modelling of Incompressible Elastic Thin Plastic Plate (Global Journal of Science Frontier Research, 2012)
The aim of this work to study the asymptotic behavior of an elasticity problem, of containing structure, in incompressible elastic thin oscillating layer of thickness and stiffness depending of small parameter. We use the epi-convergence method to approximate the limit problem modeling.
Keywords: Limit behavior; elasticity problem; epi-convergence method; global subadditive theorem; limit problems 1